A new species of Cnodalomyia Hull, 1962 (Diptera, Asilidae, Asilinae) from Brazil - Lamas, Carlos José Einicker; Mellinger, Gabriela Bastos (Zootaxa, 2008)
The robber fly genus Cnodalomyia Hull, 1962 is a monotypic member of the Asilinae. The type species, C. obtusa Hull, is endemic to Itatiaia, State of Rio de Janeiro, Brazil. A new species, Cnodalomyia catarinensis sp. nov. from southern states of Brazil (Santa Catarina, Paraná and São Paulo) is herein described and illustrated. Both species are restricted to highland areas of the Atlantic Forest. An identification key to the species is also presented.